Preparation of scale inhibitor by using the waste of refined 2‐acrylamido‐2‐methylpropane sulfonic acid. Issue 3 (8th January 2016) - Guo, Wenya; Gao, Canzhu; Li, Qimeng; Cheng, Zhongfa; Qi, Xiaojing
Abstract : Acrylic acid‐2‐acrylamido‐2‐methylpropane sulfonic acid (AA‐AMPS) is a kind of copolymer with good scale and corrosion inhibition performance. Refining of AMPS produces refined residue, which belongs to hazardous waste and must be properly treated and disposed. In this work, the refined residue was reused as the raw material to synthesize scale inhibition copolymer with the addition of AA. The chemical construction and thermal properties of copolymers were confirmed by NMR, FTIR, and thermogravimetry analysis (TGA). To achieve a comprehensive and systematic understanding of copolymers, the inhibition behavior of CaCO3, Ca3 (PO4 )2, and CaSO4 were examined through static scale inhibition tests. The capability of ferric oxide dispersion was also determined. The results of structural analysis were consistent with the expected structures. Static experiments were observed that scale inhibition of Ca3 (PO4 )2 and CaSO4 was excellent and the scale inhibition rate was close to 100% when the concentration of AA‐AMPS was 30 mg L −1 . It was noticed that the performance of copolymers synthesized with AMPS residue appeared nearly no different than when AA‐AMPS was synthesized with normal materials. The results show that the refined AMPS residue could be reused as raw material to prepare scale inhibitor copolymer. Significance : Refined residue of AMPS was used to synthesize scale inhibition copolymer in this work. It would bring serious damage to society and environment if the hazardous waste refined residue cannot be properly treated and disposed. This study shows that the reuse of refined residue could achieve the goals of making use of waste and save the resources. This reuse technology develops a new way to reuse the hazardous waste and it would provide both economical and environmental benefits. © 2016 American Institute of Chemical Engineers Environ Prog, 35: 833–839, 2016